Implementation of the Role Play Model in Improving the Speaking Ability of the Fourth-grade Students of Madrasah Ibtidaiyah Nurul Huda, Tangerang Regency - Sunarno; Setiawan, Aris (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2022)
The purpose of the results of this study is to obtain the effect of the role-play model on children's abilities. And want to know the difference before and after playing the game. The research method uses a quantitative approach that tests based on statistics. Data collection techniques through the distribution of questionnaires, interviews, and observations. inventory, scale, and size. Data processing such as grouping data based on the type collected from respondents, making tabulations, and calculating hypothesis testing. (1). So there is a significant effect of the role-play model on students' speaking ability. It can be seen that the correlation level is 93.2%. (2). There are differences in students' speaking abilities, before and after using the role-play model game. Because from the results of hypothesis testing the signivicant value is equal to 0.000 where the signivicant value becomes smaller than 0.05.